Covalent Inhibition of New Delhi Metallo‐β‐Lactamase‐1 (NDM‐1) by Cefaclor. Issue 17 (10th October 2014) - Thomas, Pei W.; Cammarata, Michael; Brodbelt, Jennifer S.; Fast, Walter
Abstract Covalent irreversible inhibitors can successfully treat antibiotic‐resistant infections by targeting serine β‐lactamases. However, this strategy is useless for New Delhi metallo‐β‐lactamase (NDM), which uses a non‐covalent catalytic mechanism and lacks an active‐site serine. Here, NDM‐1 was irreversibly inactivated by three β‐lactam substrates: cephalothin, moxalactam, and cefaclor, albeit at supratherapeutic doses (e.g., cefaclor KI=2.3±0.1 mM; kinact=0.024±0.001 min−1). Inactivation by cephalothin and moxalactam was mediated through Cys208. Inactivation by cefaclor proceeded through multiple pathways, in part mediated by Lys211. Use of a cefaclor metabolite enabled mass spectrometric identification of a +346.0735 Da covalent adduct on Lys211, and an inactivation mechanism is proposed. Lys211 was identified as a promising "handhold" for developing covalent NDM‐1 inhibitors and serves as a conceptual example for creating covalent inhibitors for enzymes with non‐covalent mechanisms.